SURVEI PENGGUNAAN E-MODUL SEBAGAI BAHAN AJAR BIOLOGI DI KELAS X SMAN 3 SIAK HULU - Edo Praguna; Suryanti; Nurkhairo Hidayati (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This research is motivated by the low use of electronic teaching materials, so that students are less active in the learning process and students find it difficult to understand the concepts of biology subjects. The aim of this research is to determine the use of e-modules as teaching materials in biology subjects. This research uses a quantitative descriptive method using research instruments, namely observation sheets, interviews and questionnaires. The results of this research indicate that students need to use e-modules in biology class subjects X SMAN 3 Siak Hulu Based on the results of observations, interviews and filling out questionnaires, it shows that e-modules are needed by students with a percentage of 73.33%, so it can be concluded that this is based on students' habits and needs when studying using technology such as smartphones, laptops, computers, or technology-based media can access the e-module.